Association Between Fine Particle Waves and Sexual Function: A Nationwide Cross-Sectional Survey in China - Weiqian Zhang; Rui Qu; Guan Cheng; Jingxuan Wang; Tailang Yin; Jue Liu; Dongdong Tang; Yan Zhang (Toxics)
Background: The effect of the long-term persistently elevated air pollutants, often referred to as air pollution waves, on sexual function has not been sufficiently addressed. Methods: This nationwide cross-sectional study involved 12,157 participants, with 5496 females and 5039 males. PM waves were characterized by daily average PM concentrations surpassing Grade II thresholds of China’s ambient air quality standards (PM2.5 > 75 μg/m3, PM10 > 150 μg/m3) for three or more consecutive days (3–8 days). Male sexual function was assessed through the International Index of Erectile Function-5 (IIEF-5) and the Premature Ejaculation Diagnostic Tool (PEDT), while female sexual function was evaluated using the Female Sexual Function Index (FSFI). A multivariate linear regression model was employed to investigate the link between PM wave exposure and sexual function. Results: Exposure to PM10 waves, defined as 3 (β = −0.0145, 95%CI = −0.0280, −0.0010), 4 (β = −0.0145, 95%CI = −0.0280, −0.0010), 5 (β = −0.0193, 95%CI = −0.0371, −0.0015), 6 (β = −0.0218, 95%CI = −0.0415, −0.0021), 7 (β = −0.0243, 95%CI = −0.0458, −0.0028), and 8 (β = −0.0243, 95%CI = −0.0458, −0.0028) consecutive days, negatively impacted IIEF-5 scores and male sexual function. Moreover, depression levels, as evaluated by the PHQ-9, played a mediating role in the connection between PM10 waves and IIEF-5 scores. The potentially vulnerable subgroups were the younger 20–30 and the low-income groups. Conclusions: Our results suggest for the first time that PM10 waves are associated with decreased IIEF-5 scores, which are mediated by depression score PHQ-9, informing policy formulation for public health interventions and individual safeguarding.